النظام القانوني للتوقيع والتصديق الإلكترونيين في التشريع الجزائري - أمجد, بن شرودة; أيمن, هزلاوي; مجدة, العوني (جامعة الوادي - University eloued, 2022)
تطرقنـا فـي هـذه المذكرة لموضـوع " النظـام الـقـانوني للتوقيـع والتصـديق الإلكتـرونيين فـي التشريع الجزائـري" الـذي يلعـب دور كبيـر فـي المعاملات الإلكترونيـة عامـة، والتجـارة الإلكترونيـة خاصـة، ناهيـك عـن المزايـا التـي يمنحهـا للمتعاملين، حيـث استعرضـنـا مـن خـلال فصـلنا الأول"النظام القانوني التوقيـع الإلكترونـي" وذلك بتوضيح مفهـوم التوقيع الإلكتروني، كمـا بينـا أيضـا نـطـاق تطبيـق التوقيـع الإلكتروني ووظائفـه، فضـلا عـن حجيتـه فـي الإثبـات وآليـات حمايتـه، وتطرقنـا أيضـاً مـن خــلال الفصـل الثـاني " التصديق الإلكتروني من المنظور القانوني"، الذي ناقشـنـا فيـه مفهـوم شـهادة التصـديق الإلكترونــي وأنواعهـا، بالإضـافة إلـى جهـات التصـديق الإلكترونــي ومـدى حجيـة التصـديق فـي الإثبات وكذا حجية الوثائق الإلكترونية في الإثبات. وعليـه وجـب علـى المشـرع الجزائـري أن يواكـب التطـور الحاصـل فـي مجـال الحوسـبة والاتصال، وأن يقوم بتعديل وإضافة نصوص قانونية تتماشى مع متطلبات العصر. In this memo, we touched on the issue of "the legal system for the internalization and authenticity of the Algerian legislation" that play a great role in general electronic transactions, and the electronic trade in particular, not to the advantages that it gives to the dealers, so we reviewed us from the first semester of the "legal system" The electronic signature, as well as the cultivation of electronic signing of the electronic signing, as well as its argument in the proven installations and the mechanisms of its protection, and we also touched on the second chapter "electronic certification from the legal perspective", in which we discussed the concepts of the electronic certification certificate and their types, in addition to the electronic confrontations and their types, in addition to the electronic confrontations and their types, to the electronic confrontations and their types, in addition to the electronic confrontations and their types, to the electronic confrontations and their types, to add to the electronic. Authentication in the evidence, as well as the authenticity of electronic documents in the evidence. The Algerian legislature must keep pace with developments in the area of computing and communication, and amend and add legal texts that are in line with today's requirements.
مذكرة ماستر
Keywords: التوقيع الالكتروني، التصديق الالكتروني، الرقمنة; Electronic signature, electronic certification, digitization